Results of Photo(chemo)therapy Applications Survey in Turkey - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2010)
Phototherapy Group created a comprehensive questionnaire in 2009 consisting of 31 questions in an attempt to determine the current state of photo(chemo)therapy applications in Turkey. The questionnaire was sent to Phototherapy Group members and to all institutions with dermatology residency programmes. Thirty six centres participated in the survey. The results of the survey are presented.
Keywords: Phototherapy; photochemotherapy; survey; Turkey; GUIDELINES; MONOCHROMATOR; DOSIMETRY; WORKSHOP